Situational analysis of prevailing practices in the management of first‐episode psychosis in Chennai, India. Issue 3 (21st May 2020) - Dhandapani, Vijaya Raghavan; Ramachandran, Padmavati; Mohan, Greeshma; Chandrasekaran, Sangeetha; Paul, Vimala; Pattabiraman, Ramakrishnan; Mohan, Mohapradeep; Iyer, Srividya; Rangaswamy, Thara; Singh, Swaran Preet
Abstract : Aim: This paper aims to examine how existing mental health within the city of Chennai, India manages first‐episode psychosis, to determine lacunae and barriers in providing effective early intervention and to make appropriate recommendations to improve the care of first‐episode psychosis patients. Methods: Interviews were held with 15 health professionals to capture information on current practices and facilities available for the management of first‐episode psychosis. Results: No specialized clinic or services were available for individuals with first‐episode psychosis in Chennai, except one. Pharmacotherapy was the main treatment modality with psychological support to patients and families. Most common drugs used were Risperidone, Olanzapine, and Haloperidol in their recommended doses. General practitioners and paediatricians, due to inadequate training in mental health, referred patients with psychosis to mental health professionals. Conclusions: Equipping the existing mental health services to manage FEP and training all health professionals on psychosis will improve FEP management in Chennai.